A New Algorithm for System of Integral Equations - Abdujabar Rasulov; Adem Kilicman; Zainidin Eshkuvatov; Gulnora Raimova (Abstract and Applied Analysis)
We develop a new algorithm to solve the system of integral equations. In this new method no need to use matrix weights. Beacause of it, we reduce computational complexity considerable. Using the new algorithm it is also possible to solve an initial boundary value problem for system of parabolic equations. To verify the efficiency, the results of computational experiments are given.